Pemberian ASI Esklusif dengan Pencegahan Stunting pada Bayi Usia 0-6 Bulan - Diyah Ayu Safitriy; Yulia Paramita Rusady (PT. PENERBIT TIGA MUTIARA, 2026)
Stunting is a chronic nutritional problem that occurs as a result of prolonged inadequate nutrient intake, beginning as early as the prenatal period, and leading to impaired physical growth and cognitive development in children. This condition remains a strategic public health issue because it has direct implications for the quality of human resources and national competitiveness in the future. This study focuses on the role of the family, particularly pregnant women and breastfeeding mothers, in preventing stunting through adequate nutritional fulfillment during the first 1,000 days of life, with an emphasis on exclusive breastfeeding practices. The method employed is a conceptual review based on scientific literature and relevant health policies to analyze the relationship between early nutritional adequacy and the risk of stunting in children. The findings indicate that stunting not only results in children having a height below the age-standard norm, but also disrupts brain development, which in turn affects learning ability, productivity, creativity, and children’s readiness to face future educational and social challenges. Family-based approaches to stunting prevention have proven effective, as the family represents the primary and earliest environment for meeting children’s nutritional needs. Exclusive breastfeeding during the first six months of life emerges as a key strategy, as it optimally fulfills infants’ nutritional requirements and reduces the risk of malnutrition. The conclusion of this study emphasizes that strengthening the role of the family through nutritional education for pregnant and breastfeeding mothers is a strategic step toward sustainable stunting prevention. The novelty of this scientific work lies in its integrative emphasis on family-based approaches and the optimization of exclusive breastfeeding as a foundation for improving human resource quality from early life, encompassing not only physical, but also cognitive, emotional, and social dimensions of child development.